Inventarisasi Jenis Semut (Hymenoptera: Formicidae) di Kebun Kakao Desa Rahmat, Kecamatan Palolo, Kabupaten Sigi, Sulawesi Tengah - Aprillia Ardhi Kenzha Cahya Ningrum (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Ants (Hymenoptera: Formicidae) are social insects that play an important role in ecosystems, including agroecosystems such as cacao plantations. Their presence serves as an indicator of environmental and soil quality, and they function as biological control agents, decomposers of organic matter, and seed dispersers. This study aimed to inventory ant species found in the cacao plantation of Rahmat Village, Palolo Subdistrict, Sigi District, Central Sulawesi. The research was conducted from April to June 2024 at the Edufarmers demonstration plot in Rahmat Village. Sampling was carried out using hand collecting methods and pitfall traps methods. Specimens were identified based on morphological characteristics using the identification guidebook "A Guide to the Ants of Jambi (Sumatra, Indonesia)”. The results identified 346 ant individuals belonging to 4 subfamilies and 14 genera, namely Formicinae (Camponotus, Anoplolepis, Paratrechina, Cladomyrma, Polyrhachis), Dolichoderinae (Tapinoma, Philidris), Myrmicinae (Solenopsis, Carebara, Tetramorium, Monomorium, Pheidole), and Ponerinae (Ponera, Odontomachus). The most dominant genus found was Camponotus with 105 individuals, while the least represented genera included Tapinoma and Pheidole, each with only one individual.
Entry oleh Arif 2026 Maret 26
Keywords: Ants; Cacao; Hand Collecting; Pitfall Trap